Capital Structure and ESG Risk Rating on Firm Value with Profitability as a Moderating Variable - Yuyun Oktaviana; Acep Komara (MASI Mandiri Edukasi, 2026)
Previous studies regarding the combined effect of financial decisions and sustainability risks on firm value show inconsistent results, creating a research gap. This study examines the direct effect of capital structure and ESG risk rating, vital in Indonesia's capital market, on firm value, and the moderating effect of profitability. This research used cross-sectional data from 85 companies listed on the IDX in 2024. The sample was adjusted to 47 companies because the initial data was not normally distributed; thus, outlier elimination using the boxplot method was performed to normalize it. Analysis used cross-sectional regression and Moderated Regression Analysis (MRA) using Stata 17. Results indicate a positive and significant direct effect of capital structure on firm value. However, the ESG risk rating found no significant effect on firm value. Furthermore, capital structure on firm value moderated by profitability showed insignificant results. Meanwhile, ESG risk rating on firm value with profitability as a moderating variable proved positive and significant. These findings confirm that profitability can strengthen the effectiveness of ESG risk management in increasing firm value. Practically, corporate managers must maintain profitability to ensure ESG initiatives optimally impact market value, while investors can use these combined metrics to identify high-quality assets.